Meriam Karbit in Kapuas Riverbank Communities: An Urban Sociology Study - Chintya, Dina; Purnama, Desca Thea; Juliansyah, Viza; Annisa, Siti; Trina, Fitra Maria; Dhea, Dhea; Ira, Ira (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to find out meriam karbit in the people on the tepian sungai kapuas. This research is descriptive qualitative research. The data used in this study is primary data, sampling using a purposive sampling technique, amounting to 3 respondents. For data collection using observation, interviews, and documentation. The data analysis used by Haberman and Mile is data reduction, display, drawing conclusions, and data triangulation. The results of this study indicate that the meriam karbit tradition has social and economic impacts, socially it forms community solidarity, economically it becomes the main and side livelihood of the community.